Investigating lecturers’ use of socio-affective strategies for ESL students’ speaking motivation and speech fluency: a pilot study / Nurul Amilin Razawi and Faizah Mohamad - Razawi, Nurul Amilin; Mohamad, Faizah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Developing effective speaking skills in English as a Second Language (ESL) classrooms remains a significant challenge for students in Malaysia due to anxiety, lack of motivation, and limited practice opportunities. This pilot study explores the feasibility of investigating the lecturers’ use of socio-affective strategies to enhance ESL students’ speaking motivation and speech fluency at a public university in Malaysia. It was observed that some students who enrolled in English for Oral Communication course at a Malaysian public university were struggling with speaking motivation and speech fluency when delivering speeches in class. This study aimed to assess the feasibility of large-scale research on using socio-affective strategies and gathered preliminary data on lecturers’ perceptions of using the strategies in teaching ESL speaking. A mixed-methods design was employed, involving 30 participants in the quantitative phase and 2 participants in the qualitative phase. In the quantitative phase, the findings revealed that lecturers used various socio-affective strategies in the speaking classroom focusing on collaborative learning, interactive instruction, showing empathy and emotional support, strategic feedback, anxiety reduction through rehearsals, authentic practice, and incorporating technology for classroom engagement and pronunciation skill development. It was also discovered that the use of socio-affective strategies was not influenced by gender. Qualitative data further complemented lecturers’ experiences and justifications in using socio-affective strategies. A validated questionnaire and semi-structured interview sheet showed high reliability and validity, making them suitable for large-scale studies. This pilot study sets a strong basis for in-depth research in investigating the lecturers’ use of socio-affective strategies in ESL speaking classrooms and offers insights into the theoretical and practical application of ESL pedagogy.